Corrosion Factors on Nail - Titania Natasya; Muthia Embun Khairafah; Murna Sari Br Sembiring; Laura Nazrifah Hutabarat (Universitas Negeri Medan, 2022)
Corrosion is a chemical phenomenon in metal materials that can occur due to physical, chemical or biological processes. Physical processes are characterized by the destruction of metal morphology, chemical processes are characterized by chemical processes that occur in metals, and biological processes are characterized by the activity of destructive bacteria on metals. In this practicum, corrosion experiments were carried out on nails. The subjects in this study were 6 nails. This research was conducted by quantitative method, namely Experiment. The experimental method is a quantitative research method used to determine the effect of the independent variable (treatment) on the dependent variable (outcome) under controlled conditions. The result of his research is that the fastest and most visible corrosion is in plastic cups which are given hot water as a medium.